Business model innovations and their relationship with sustainable development in agribusiness: a bibliometric analysis - Estácio, Rita (2025)
This article identifies the main links, commonalities, and future interdisciplinary topics between business model innovations and sustainable development in agribusiness. A systematic bibliometric analysis of the literature on business model innovations related to sustainable development in agribusiness was carried out using RStudio – Biblioshiny for Bibliometrix. Two hundred and fifty-one documents published in journals indexed in Scopus and Web of Science were analyzed between 2001 and 2023. Business model innovations and sustainable development in agribusiness are seen as ways of responding to social, economic, and environmental challenges. The research also reveals that when sustainable development is the topic, innovations in business models tend to incorporate practices that seek profitability and minimization of environmental and social impacts, promoting corporate social responsibility and long-term sustainability. There is a growing consensus that purely profit-focused business models have considerable limitations in neglecting social business activities and environmental impacts. About the question, “What are the innovations in business models that can improve sustainable development in agribusiness?”, the literature provides no practical answers. The next steps, therefore, are to identify and analyse successful case studies.